2016
DOI: 10.1001/jamaoncol.2015.5252
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department–Initiated Palliative Care in Advanced Cancer

Abstract: clinicaltrials.gov Identifier: NCT01358110.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
269
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(292 citation statements)
references
References 31 publications
3
269
0
16
Order By: Relevance
“…4348 Specifically, although prior studies of early palliative care have shown improvement in patient-reported QOL, symptom burden, and mood, 4348 the current trial demonstrates that early integrated palliative care ameliorates the risk of PTSD symptoms as well. These findings expand our knowledge about the potential benefits of palliative care for patients with hematologic malignancies and those receiving potentially curative therapy with HCT who were excluded from prior palliative care trials in oncology.…”
Section: Discussionmentioning
confidence: 74%
“…4348 Specifically, although prior studies of early palliative care have shown improvement in patient-reported QOL, symptom burden, and mood, 4348 the current trial demonstrates that early integrated palliative care ameliorates the risk of PTSD symptoms as well. These findings expand our knowledge about the potential benefits of palliative care for patients with hematologic malignancies and those receiving potentially curative therapy with HCT who were excluded from prior palliative care trials in oncology.…”
Section: Discussionmentioning
confidence: 74%
“…Three of the eight studies (38%) showed a small significant effect [36][37][38] and four (50%) a non-significant effect in favour of specialist palliative care [30][31][32][33] regarding the study specific assessment tools for quality of life (table 3).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Grudzen et al 37 published the most current randomised controlled trial that we included. In this elaborate adequately powered trial (n=136), the authors included patients with cancer but initiated specialist palliative care consultation (intervention group) only for those patients who were referred to the emergency department (control was consultation on request of the emergency physicians).…”
Section: Total ( % Ci)mentioning
confidence: 99%
“…Palliative care integration early in the disease course can help to address these aggressive end-of-life interventions and improve patients’ quality of life in other advanced cancer settings(13-18), but the unpredictable nature of blood cancers and the general attitudes of some hematologic oncologists towards palliative care provide several barriers to increased access(7, 19-21). Despite these barriers, a trend towards increased palliative care referral has been observed(22), along with a renewed call to examine the intersection between palliative care and the quality of life of blood cancer patients(23, 24), especially amid initial evidence of feasibility and efficacy in subpopulations such as those undergoing stem cell transplantations(25).…”
Section: Introductionmentioning
confidence: 99%